Poster Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.2230
|View full text |Cite
|
Sign up to set email alerts
|

Fri0277 ischemic and Systemic Symptoms in Giant Cell Arteritis Patients, Response to Tocilizumab

Abstract: BackgroundIn Giant Cell Arteritis (GCA) two dominant cytokine clusters have been linked to disease activity, IL-6 – IL-17 axis (Th17) and IL-12 – IFN γ axis (Th1). The first one related to systemic symptoms and the second route responsible for ischemic symptoms. Tocilizumab (TCZ) performs its effect mainly by inhibiting Th17 axis and terminally Th1 route.ObjectivesOur aim was to evaluate the effect of TCZ on ischemic and systemic symptoms throughout the follow-up.MethodsRetrospective, multicenter study of 134 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The results of several open uncontrolled observation studies of TCM in GCA at "real life" (usual clinical practice) are published, too [7,8,9,10,16,42,52,58]. On the basis of a considerable material (n = 307) the effects of TCM obtained by the controlled studies, were confirmed.…”
Section: Interleukin-6-inhibitorsmentioning
confidence: 80%
See 2 more Smart Citations
“…The results of several open uncontrolled observation studies of TCM in GCA at "real life" (usual clinical practice) are published, too [7,8,9,10,16,42,52,58]. On the basis of a considerable material (n = 307) the effects of TCM obtained by the controlled studies, were confirmed.…”
Section: Interleukin-6-inhibitorsmentioning
confidence: 80%
“…При пациентите, третирани с ТЦМ, втората предпоставка отпада -производството на ОФреактанти от хепатоцитите се стимулира от IL-6, а последният е блокиран функционално от ТЦМ. Остава да се разчита на прецизно снетите анамнеза и статус за наличие на клинични признаци: възобновено или с нова локализация главоболие, повишена температура, умора, нощно изпотяване, клаудикация на масетерите и/или езика, симптоматика на ревматична полимиалгия, палпаторна болезненост на a.temporalis и/или отслабване на пулсациите ѝ, хиперестезия на скалпа, намалени пулсации/RR на горни крайници, очна или симптоматика от страна на ЦНС [9,10,21,47,50,53,56]. Поради споменатите особености в темпа на промените на изобрази-телните находки чрез MRI, CT, PET/CT на тях не би могло да се разчита.…”
Section: табица 5 тоцилизумаб в лечението на гка (Villger Et Al фаза II рандомизирано двойносляпо плацебо-контролирано проучване 2016)unclassified
See 1 more Smart Citation